PEMODELAN GRAFIK PENGENDALI TOTAL DAN RATAAN DISKRIT UNTUK GENERALISASI DISTRIBUSI GEOMETRIK - Sudarno, Sudarno; Mukid, Moch. Abdul (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Total events which do by counting will be obtained discret data type. The discret data type and geometric distribution could be drawn by total number of events chart (G chart) and average number of event chart (H chart). In this research result upper control limit, center line, and lower control limit, both G chart and H chart. Data processing of the case, resulting G chart that upper control limit is 80.77 and center line is 39.8, meanwhile by H chart obtained that upper control limit and center line, respectively, 11.54 and 5.8. The results of G chart and H chart could be used for prediction events at the future to anticipate the real problems. Therefore, the systems have no problem and their activities will be dynamic, stable and best perform.Â Keywords:Geometric Distribution, Total Number of Event Chart, Average Number of Event Chart